2015
DOI: 10.1016/j.apsusc.2015.06.087
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of ultrasound assisted “graphene oxide–magnetite” hybrid, and investigation of its adsorption properties for Sr(II) and Co(II) ions

Abstract: a b s t r a c tMagnetite nanoparticles with a size distribution of 15-21 nm were synthesized and decorated onto surface of graphene oxide by ultrasound assisted precipitation. Size and size distribution of the obtained M-GO hybrid were appreciably finer than the hybrids prepared by stirring method. M-GO is a superparamagnetic material with saturation magnetization of 31 emu g −1 . The Langevin equation was successfully applied for estimation of size of Fe 3 O 4 nanoparticles in M-GO hybrid, with maximum error … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(41 citation statements)
references
References 61 publications
3
38
0
Order By: Relevance
“…In recent years, graphene oxide nanomaterials, which has a large theoretical surface area and high sorption capacity for the metallic cations, has with wide range of surface oxygen-containing functional groups such as hydroxyl, epoxy, and carboxyl [9,10] . According to literature, graphene oxide has a notable affinity toward hard and semi-hard cations like uranium, thorium, lanthanides, and also strontium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, graphene oxide nanomaterials, which has a large theoretical surface area and high sorption capacity for the metallic cations, has with wide range of surface oxygen-containing functional groups such as hydroxyl, epoxy, and carboxyl [9,10] . According to literature, graphene oxide has a notable affinity toward hard and semi-hard cations like uranium, thorium, lanthanides, and also strontium.…”
Section: Introductionmentioning
confidence: 99%
“…These superior properties make graphene oxide proper for efficient adsorbent of cesium and strontium. Unfortunately, disadvantage of the graphene oxide is colloidal behavior of its dispersion, which makes separation of its reaction products with metallic cations quite unfairable [9] . Preparation of composite is one of the possible solutions to solve this problem.…”
Section: Introductionmentioning
confidence: 99%
“…The Zeta potential of GO and GO‐EDTA composite was determined at different pH values (4, 6, and 9) as seen in Table . From these results it can be concluded that the Zeta potential of GO and GO‐EDTA surface is negative charge and has good stability according to B. Salopek et al The aforementioned pH dependency of the uptake curves could be explained by two mechanisms as follow: (1) the surface charge change of the GO adsorbent, and (2) the changes in cations speciation at high values of pH . The low pH value (ca.…”
Section: Resultsmentioning
confidence: 89%
“…A comparison between Fe 3 O 4 /titanate bers and some other reported magnetic composites for Sr(II) adsorption was conducted and the results were presented in Table 1. [32][33][34][35][36][37][38][39][40][41] It can be seen that the magnetic titanate nanobers exhibits excellent adsorption ability among magnetic composite used for Sr(II) removal. Although some magnetic adsorbents, such as magnetic polyaniline/graphene oxide, magnetic Sr(II)-imprinted polymer, shows high adsorption capacity towards Sr(II) as well, Fig.…”
Section: Comparison Of Various Magnetic Adsorbentsmentioning
confidence: 99%